Association between insurance status at diagnosis and overall survival in chronic myeloid leukemia: A population‐based study. Issue 13 (2nd May 2017) - Perry, Ashley M.; Brunner, Andrew M.; Zou, Tao; McGregor, Kristin L.; Amrein, Philip C.; Hobbs, Gabriela S.; Ballen, Karen K.; Neuberg, Donna S.; Fathi, Amir T.
Abstract : BACKGROUND: Chronic myeloid leukemia (CML) can be treated effectively with tyrosine kinase inhibitor therapy directed at BCR‐ABL, but access to care, medication cost, and adherence may be barriers to treatment. This study was designed to determine whether the insurance status at diagnosis influences CML patient outcomes. METHODS: The Surveillance, Epidemiology, and End Results database was used to identify 5784 patients, aged 15 years or older, who were diagnosed with CML between 2007 and 2012 and whose insurance status was documented at diagnosis. The primary outcome was 5‐year overall survival (OS). Covariates of interest included the age at diagnosis, race, ethnicity, sex, county‐level socioeconomic status, and marital status. OS was evaluated with a log‐rank test and Kaplan‐Meier estimates. RESULTS: Among patients aged 15 to 64 years, insurance status was associated with OS ( P  < .001): being uninsured or having Medicaid was associated with worse 5‐year OS in comparison with being insured (uninsured patients, 72.7%; Medicaid patients, 73.1%; insured patients, 86.6%). For patients who were 65 years old or older, insurance had less of an impact on OS ( P  = .07), with similar 5‐year OS rates for patients with Medicaid and those with other insurance (40.2% vs 43.4%). In a multivariate analysis of patients aged 15 to 64 years, both uninsured patients (hazard ratio [HR], 1.93; P  < .001) and Medicaid patients (HR, 1.83; P  < .001) had an increased hazard of death in comparison with insured patients; patients younger than 40 years, female patients, and married patients also had a lower hazard of death. CONCLUSION: These findings suggest that CML patients under the age of 65 years who are uninsured or have Medicaid have significantly worse survival than patients with other insurance coverage. Cancer 2017;123:2561–69. © 2017 American Cancer Society . Abstract : Although chronic myeloid leukemia can be effectively treated with targeted therapies, access to these agents may vary with the insurance status. This article identifies an association between being uninsured or having Medicaid and having worse survival in comparison with insured persons with a new chronic myeloid leukemia diagnosis. See also pages 2395‐7.